GOOD CORPORATE GOVERNANCE DAN MANAJEMEN RESIKO DI BANK SYARIAH - Rita Mulyani (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
By applying the principles of good corporate governance and risk management, Islamic banks have won the trust of the public by significantly increasing the number of Islamic bank customers, although not as much as conventional bank customers. To build public trust in Islamic banks, in addition to GCG, there is also a need for good management and risk management of Islamic banks. It is hoped that Islamic banks will be able to play an active role in banking activities in Indonesia as an indicator of whether or not the economic conditions in Indonesia. The role of corporate governance has been far applied in the teachings of Islam. The principles of Good Corporate Governance which consist of transparency, accountability, responsibility, professional and fairness are contained in sharia values ​​which intensely consist of: (1) shiddiq (honesty), (2) trust (fulfillment of trust), (3) fathanah (intelligence), (4) tabligh (transparency, openness). The important thing that needs to be done by Islamic banks is to build an effective risk management culture, so that banks have competitiveness and survive in economic conditions that are full of uncertainty or even crisis. The types of risks faced by Islamic banks include the following: 1) Financing Risk, 2) Liquidity Risk, 3) Interest Rate Risk, and 4) Operational Risk.